Prevalence and genetic characterisation of microsporidia among immunocompromised patients in Malaysia / Nur Amirah Hassan - Nur Amirah , Hassan (2018)
While information with regards to the bacterial and viral infection is commonly available among clinicians, data on parasitic infection, particularly microsporidia among immunocompromised patient is currently lacking in Malaysia. Most of the epidemiological study of microsporidia has relied on conventional microscopy technique, which does not differentiate parasite at the species level. The present study was carried out to identify microsporidian species in various groups of immunocompromised patients. From March 2016 to March 2017, a total of 342 archived stool samples were examined microscopically for microsporidian spores using Gram-chromotrope Kinyoun (GCK) staining. Positive stool samples by microscopy were subjected to polymerase chain reaction (PCR) and sequencing for species identification. Based on microscopy examination, the overall prevalence of microsporidian infections was 28.9% (99/342; 95% CI=24.4-34). The prevalence of microsporidia were significantly higher among males (32.7%; 95% CI=27-39) compared to females (21.6%; 95% CI=15.1-30) (p=0.031). The highest prevalence was recorded in autoimmune diseases patients (62.5%; 95% CI=30.6-86.3), followed by end-stage renal failure (ESRF) patients (52.9%; 95% CI=39.5-66.0), cancer patients (31.9%; 95% CI=22.1- 43.6), human immunodeficiency virus (HIV/AIDS) patient (27.7%; 95% CI=20.5-36.4) and organ transplant recipients (22.2%; 95% CI=10.6-40.8). Meanwhile, the lowest prevalence of microsporidian infections was reported in acute gastroenteritis (AGE) patients (11.3%; 95% CI=5.29-22.6). Other intestinal parasites reported among these patients were Abstract ii Strongyloides stercoralis, Trichuris trichiura, Ascaris lumbricoides and Cryptosporidium species. Diarrhoea was the most common symptoms among patients with microsporidiosis. Of these positive stool samples by microscopy, 50 samples were successfully amplified and confirmed as Enterocytozoon bienuesi. No Encephalitozoon intestinalis was detected. The highest prevalence of E. bienuesi was recorded in organ transplant recipients (6/6; 100%) and autoimmune patients (5/5; 100%), followed by AGE patients (5/6; 83.3%), HIV/AIDS patients (16/33; 48.5%), cancer patients (9/22; 41%), and ESRF patients (9/27; 33.3%), respectively. Phylogenetic analysis revealed that zoonotic and inter-human transmission may be a possible route of transmission for microsporidian infections among these patients. Three different mismatches were reported within the E. bieneusi isolates which speculated the existence of genetic diversity in the E. bieneusi species. Accurate identification of species might help clinicians to decide appropriate management strategies as dissemination risks, and treatment response varies for different species, hence improving the management of microsporidian infections.